2020
DOI: 10.1590/s1808-185120201903236062
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Dynamic Surgical Guidance Assist Accurate Pedicle Screw Placement in Patients With Osteoporosis or Osteopenia?

Abstract: Objective To compare the use of a dynamic surgical guide (PediGuard®) and pilot hole preparation, with the use of a probe and the aid of fluoroscopy in osteoporotic or osteopenic patients undergoing pedicular fixation of the thoracic or lumbar spine. Methods One hundred and eight patients were randomized. A pilot hole was prepared with the dynamic surgical guide (PediGuard®), or with a probe with the aid of fluoroscopy. A total of 657 vertebral pedicles (120 thoracic and 180 lumbar) were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Kageyama et al 16 showed a 98% accuracy in retrospective lumbar surgeries with ECD and multi-axis angiography unit. For prospective randomized controlled trials, Bai et al, 34 Suess et al, 35 Defino et al, 36 Lebhar et al, 37 and Bhogal et al, 38 documented the accuracy from 85% to 97.4%, and shows that ECD increases pedicle screw accuracy, especially in scoliosis surgeries. New applications and techniques have been designed for ECD.…”
Section: Safety and Effectiveness Of The Modified Ecd Withmentioning
confidence: 99%
“…Kageyama et al 16 showed a 98% accuracy in retrospective lumbar surgeries with ECD and multi-axis angiography unit. For prospective randomized controlled trials, Bai et al, 34 Suess et al, 35 Defino et al, 36 Lebhar et al, 37 and Bhogal et al, 38 documented the accuracy from 85% to 97.4%, and shows that ECD increases pedicle screw accuracy, especially in scoliosis surgeries. New applications and techniques have been designed for ECD.…”
Section: Safety and Effectiveness Of The Modified Ecd Withmentioning
confidence: 99%